The effect of chronic 1,2,3,4-Tetrahydroisoquinolines administration in young spontaneously hypertensive rats - Abdullah, Aszrin; Abdul Razak, Tariq; Mohd Noor, Noriah (2011)
Adrenaline plays a role in the pathogenesis of essential hypertension through excessive stimulation of adrenomedullary hormonal system. Pharmacological inhibition of adrenomedullary hormonal system should result in chronic, sustained blood pressure(BP) reduction. We propose the use of 1,2,3,4-tetrahydroisoquinolines (THIQ) as a phenylethanolamine N-methyltransferase (PNMT) inhibitor in young spontaneously hypertensive rats will result in sustained BP reduction. 14 young male and female SHRs weighing between 160 and 270g were studied. Eight study rats administered with daily THIQ (Treated) and 6 age-matched controls (Control) were included. Indirect systolic blood pressure (SBP) was measured by tail cuff method prior to drug study (baseline), 2-hours post-administration on D1, D3 (subchronic), D7 and D14. The mean baseline SBP in Treated and Control SHRs were 163.15 + 16.26 vs 171.69 + 17.27 mmHg respectively (p=1.00). The mean SBP at D7 were 128.31 + 19.36 vs 173.06 + 19.62 mmHg respectively (p=0.035). The mean SBP at D14 were 129.00 + 13.34 vs 180.08 + 14.59 mmHg respectively (p=0.041). There was no significant difference in the mean weight and age of the two groups throughout the study duration. Chronic 1,2,3,4-tetrahydroisoquinolines administration is an effective inhibitor of phenylethanolamine N-methyl transferase, the enzyme that catalyzes the terminal step in the biosynthesis of adrenaline, thereby resulting in sustained BP reduction in young spontaneously hypertensive rats.